Psychological Well-Being Istri yang Tinggal Bersama Mertua di Kampung Pengasinan Kidul, Kabupaten Serang - Nada Tsana Fatinah; Elsa Fitria; Hanifatunnisa Hanifatunnisa; Uun Unayah; Peni Ramanda (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
In the context of Indonesian culture, living with parents or in-laws is quite common, especially for young couples who are not yet financially independent. However, dynamics in the household such as differences in values, habits, and privacy boundaries often pose psychological challenges for wives. This study aims to describe the psychological well-being of wives who live with their in-laws after marriage. This study uses a qualitative approach with an in-depth interview method with one of the informants who meets the criteria, namely women who have been married and have lived with their in-laws for at least one year. The results of the study indicate that there are various aspects of psychological well-being that are influenced by the condition of living with in-laws, including self-acceptance, autonomy, positive relationships with others, and mastery of the environment. Factors such as partner support, open communication, and adaptability are the main determinants in maintaining the psychological well-being of wives in this situation. This study is expected to provide insight for young couples and families in building harmonious relationships in a household involving more than one generation..